2017
DOI: 10.1016/j.actamat.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution and magnetic properties of binder jet additive manufactured Ni-Mn-Ga magnetic shape memory alloy foam

Abstract: This study investigatedmicrostructural evolution, phase transformation and magnetic behavior of additively manufactured magnetic shape memory alloy foam. Pre-alloyed angular Ni-Mn-Ga ball-milled powderwasbinder jet printed and sintered at 1020 °C for 4 h in both vacuum and argon atmospheres. Porosity of the manufactured foams was studied using micro-computed x-ray tomography and it was found that the relative density of the sintered parts wasabout50-60%. In the printed sample that was sintered in argon, electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(51 citation statements)
references
References 50 publications
0
51
0
Order By: Relevance
“…4b show that the chemical composition has been maintained to a large extent and the average Mn evaporation is about 1.6% with a standard deviation of 0.005 in relation to the initial Mn at.% of 31.21. This is promising, as previously manufactured AM samples [27,30,32] have shown that the fast heating and cooling in the AM processes can lead to dendrite growth and chemical inhomogeneity. The chemical composition Table 2 Chemical composition of the as-printed and the heat-treated samples measured with EDX, with the standard deviation used as the error, and Archimedes density measurement results of the samples as-printed and after further heat-treatment.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…4b show that the chemical composition has been maintained to a large extent and the average Mn evaporation is about 1.6% with a standard deviation of 0.005 in relation to the initial Mn at.% of 31.21. This is promising, as previously manufactured AM samples [27,30,32] have shown that the fast heating and cooling in the AM processes can lead to dendrite growth and chemical inhomogeneity. The chemical composition Table 2 Chemical composition of the as-printed and the heat-treated samples measured with EDX, with the standard deviation used as the error, and Archimedes density measurement results of the samples as-printed and after further heat-treatment.…”
Section: Resultsmentioning
confidence: 93%
“…As AM manufacturing methods have become more familiar, several attempts to use AM to manufacture Ni-Mn-Ga structures [27][28][29][30][31][32][33] and in other magnetocaloric materials [34] have been made. Additionally, the interaction of laser beam and Ni-Mn-Ga has been studied [35,36].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…DSC has a wide spectrum of applications ranging from simple heat of fusion evaluation() to advanced material microstructural evolution analyses and complex chemical reaction process identification . The versatility of the DSC is vast and researchers apply it to assess: coal,() cjceass,() waste,() catalysts,() minerals,() cement,() ceramics,() alloys,() and polymers.…”
Section: Applicationsmentioning
confidence: 99%